MR angiography at 7T to visualize cerebrovascular territories - Neumann, Jan-Oliver; Giese, Henrik; Biller, Armin; Unterberg, Andreas (Journal of neuroimaging, 2016)
BACKGROUND There is considerable amount of interindividual variability in the size and location of the vascular territories of the major brain arteries. More data are needed to assess the amount of variability and the possible implications for further research and patient care. Arterial spin labeling (ASL) magnetic resonance imaging has been applied in various forms to facilitate noninvasive imaging of cerebrovascular flow territories, but it requires the definition of the flow territory of interest prior to image acquisition. OBJECTIVE Assessing the vascular territories of the major brain territories by using ultra-high-field time-of-flight (TOF) magnetic resonance angiography. METHODS We have developed an alternative method to ASL by simulating cerebrovascular dye injections. Following bias field normalization and segmentation of the vessels from 7 Tesla TOF imaging, a virtual model of the arterial vessel tree was generated and a simulation of dye dispersion into the brain tissue was performed. RESULTS The results provided by our method are consistent with the data obtained by autoptic dye injection studies in 23 human beings by van der Zwan in 1993. CONCLUSION Further technical improvements in imaging and segmentation techniques will improve the accuracy of the method and will facilitate the delineation of flow territories after image acquisition on even smaller subtrees of the cerebral vasculature.
Gesehen am 16.02.2018